Model of Collaboration Between Sharia Microfinance Institutions and Banking Institutions: A Solution to the Scale Gap in Financing for Microenterprises in Indonesia - Junaidi, Heri (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
Various laws and regulations, as well as Islamic law, have provided a lot of information about the collaboration model in the financial sector, including the issue of scale gaps in the financing of Islamic Microfinance Institutions that are inadequate to support the development of ultra-micro and micro small businesses that are growing in their neighborhoods. This study examines the collaboration model of Islamic microfinance institutions that have limited capital and service coverage in supporting microenterprise development in Indonesia, while Islamic banking institutions are more oriented towards financing middle and upper-class business groups. This study aims to identify an effective collaboration model that is able to bridge the gap between the financing of Islamic microfinance institutions and Islamic banking institutions, then provide a design of a collaboration strategy that is sustainable and consistent with sharia principles to strengthen the sharia-based microfinance ecosystem. The method of this study is descriptive-exploratory qualitative, with secondary sources of data from various online media. Data collection techniques through literature studies, analysis was carried out, including data reduction, data presentation, verification, and conclusion drawing. The results of the study show that the development model of collaboration between the financing of Islamic microfinance institutions and Islamic banking in resolving the scale gap has shown a new perspective that complements the current approach. Based on this, it is necessary to modify what has been developed in the form of a productive-independent collaboration theory, where the theory is an effort to minimize the impact of microenterprises' financing dependence on Islamic Banks, which causes loss of independence. The offer is also balanced with comprehensive cooperation management, with justice and benefits for all.